2021
DOI: 10.20945/2359-3997000000419
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an interdisciplinary weight loss program on fibroblast growth factor 21 and inflammatory biomarkers in women with overweight and obesity

Abstract: Objective: To investigate the effects of an interdisciplinary intervention on biomarkers of inflammation and their relationship with fibroblast growth factor 21 (FGF21) concentrations in women with overweight and obesity. Subjects and methods: Thirty-one women were enrolled in a 12-week interdisciplinary weight loss program delivered by a team comprising an endocrinologist, nutritionist and exercise physiologist. Body composition; anthropometric measures; metabolic and inflammatory markers including adiponecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Of the 72 studies, 24 were excluded after title and abstract review, and the original text of 48 studies was reviewed. After screening the studies according to the inclusion criteria, 38 studies were excluded, and finally, 10 studies were selected ( Figure 1 ) [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 72 studies, 24 were excluded after title and abstract review, and the original text of 48 studies was reviewed. After screening the studies according to the inclusion criteria, 38 studies were excluded, and finally, 10 studies were selected ( Figure 1 ) [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The quality of four studies [ 29 , 30 , 33 , 35 ] was assessed using the RoB tool, and the results were as follows: random sequence generation (low, 1; uncertain, 2; high, 1), allocation concealment (low, 1; uncertain, 3), blinding of participants and personnel (low, 1; uncertain, 3), blinding outcome assessment (low, 1; uncertain, 3), incomplete outcome data (low, 3; high, 1), selective reporting (low, 4), and other biases (low, 1; uncertain, 2; high, 1) ( Figure 2 ). Four studies [ 26 , 27 , 28 , 31 , 32 , 34 ] were assessed by the RoBANS, and the results were as follows: selection of participants (low, 4; uncertain, 1; high, 1), confounding variables (low, 1; uncertain, 4; high, 1), measurement of exposure (low, 5; uncertain, 1), blinding of outcome assessments (low, 4; uncertain, 2), incomplete outcome data (low, 5; uncertain, 1), and selective outcome reporting (low, 5; uncertain, 1) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, one study that enrolled overweight and obese women found that changes in FGF21 levels differed among the subjects participating in the interdisciplinary intervention. Furthermore, they found that the adiponectin/leptin ratio was changed only in people with elevated FGF21 [149]. The changes in FGF21 levels after dietary interventions in different people can be used to assess the individual predisposition to weight gain over time.…”
Section: Relationship Between Fgf21 and Obesitymentioning
confidence: 99%
“…Using a blended intervention model, body weight was monitored weekly by self-report. The program is described in detail in a previous publication (27).…”
Section: Interdisciplinary Therapymentioning
confidence: 99%